Population Genetic Study Of Tapinoma Indicum (Forel) In Penang Island, Malaysia Using Microsatellite Marker Developed By Nextgeneration Sequencing - Lim, Li Yang (2022)
Tapinoma indicum Forel (Hymenoptera: Formicidae) is a household pest that is widely distributed in Asian countries. It is known as a nuisance pest that causes annoyance and disturbance by constructing nests and foraging in building for food and water. However, studies on T. indicum are limited, especially in the field of molecular biology. Hence, this research aims to study the T. indicum population genetic structure in Penang Island, Malaysia by using the novel microsatellite markers developed from whole genome of T. indium. Objectives of this research include: to determine the T. indicum population distribution in Penang island, Malaysia; to identify the phylogenetic relationship of T. indicum based on the mitochondrial gene of cytochrome c oxidase subunit Ⅰ (CO1) and 16S ribosomal DNA (16S rDNA); to design novel microsatellite marker by screening microsatellite loci of T. indicum genome sequenced from next-generation sequencing; to validate polymorphism of designed microsatellite marker; to analyse genetic diversity and population genetic structure of T. indicum using designed microsatellite markers. There was a total of 30 populations collected from Balik Pulau, Gelugor and George Town. The CO1 sequences and 16S rDNA sequences of T. indicum from each population were deposited and accessible via Genbank (NCBI) database.